PENGENALAN KOMPONEN UTAMA MESIN DAN PRAKTIK CARA PERAWATAN SEPEDA MOTOR TIPE MATIC BAGI SISWA PASRAMAN NONFORMAL KERTAJAYA TANGERANG. - I Wayan Sukania; Melynia Novita P; Elisha Elisha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Almost all work equipment or products that are used daily require maintenance. Maintenance or maintenance as a conception of all activities needed to maintain or maintain the quality of the facility/machine so that it can function properly as in its initial condition. Likewise, routine motorcycle maintenance is very important because it relates to comfort while riding and traffic safety. A survey of 15 students of the Kertajaya Tangerang Non-Formal Pasraman showed that they did not understand how to do motorcycle maintenance. Therefore, the PKM activity to introduce automatic motorcycle maintenance was welcomed. PKM activities are carried out through lecture, discussion, demonstration and practice methods so as to improve the understanding and skills of the participants. The material given includes the working principle of the main components and how to adjust them. Based on the questionnaires given before and after the training activities, it was found that there was an increase in understanding of 100% on the 10 treatment items. While on the introduction of the fault code and how to reset it, 67% of participants said they understood.